A modeling framework to meta-analyse discard survival experiments illustrated by Nephrops norvegicus in European demersal trawl fisheries - M. Morfin; E. Savina; H.P. Benoît; M. Teixeira Alves; A. Albalat; T. Catchpole; C. Fox; M. McHugh; S. Méhault; H. Nilsson; M. Oliver; D. Valentinsson; et al. (Fisheries Research, 2025)

A case study into the safety management systems for the effects of potential space weather risks, for operators of very high altitude ‘near space’ flights from Mojave Air & Space Port, California, and the associated regulatory challenges - C.T. Rees; J.R. Catchpole; A. Sewell; T. Reid; K.A. Ryden; S. Block; A. Mack (Journal of Space Safety Engineering, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

At‐vessel mortality of skates (Rajidae) taken in coastal fisheries and evidence of longer‐term survival - J. R. Ellis; G. J. Burt; G. Grilli; S. R. McCully Phillips; T. L. Catchpole; D. L. Maxwell (Journal of Fish Biology, 2018)
Data on the vigour and at‐vessel mortality (AVM) of 6798 skates (comprising Raja clavata n = 6295; R. brachyura n = 208; R. undulata n = 185, R. montagui n = 98 and R. microocellata n = 12) captured by commercial fishing vessels in the inshore waters of the southern North Sea and English Channel were recorded. AVM in longline fisheries averaged 0·44% across five vessels (0–1·47%), although skates were usually unhooked manually and did not usually pass through a bait‐stripper. AVM in otter trawls averaged 0·76% (0–2·35%), from four vessels fishing with tow durations of R. clavata caught by longline and tangle nets in better condition than those captured by otter trawl or drift trammel net. Similarly, R. undulata caught by tangle net were in better condition than those caught by otter trawl. The vigour of R. undulata was also found to be higher than other skate species for both trawl and tangle net. In total, 5283 skates were tagged with Petersen discs and released, with recapture rates for the various combinations of vessel and gear ranging up to 24·8% for R. clavata . Whilst confirming a degree of post‐release survival, quantitative estimates of post‐release mortality for skates remain unknown.

Involving stakeholders in the commissioning and implementation of fishery science projects: experiences from the U.K. Fisheries Science Partnership a - M. J. Armstrong; A. I. L. Payne; B. Deas; T. L. Catchpole (Journal of Fish Biology, 2013)
Following from similar initiatives worldwide, the U.K.'s Fisheries Science Partnership ( FSP ) was established in 2003 to provide the fishing industry with opportunities to propose and participate in scientific studies in collaboration with fishery scientists. Key concepts were that most of the available funding would support industry participation, that industry, not scientists, would come up with the ideas for projects, and that commercial fishing vessels and fishing methods would be used to address specific concerns of the fishing industry in a scientifically controlled manner. Nearly 100 projects had been commissioned by March 2012, covering annual time‐series surveys of stocks subject to traditional assessment, and ad hoc projects on, e.g . gear selectivity, discard survival, tagging and migration and fishery development. The extent to which the results of the projects have been used by stakeholders, fishery scientists and fishery managers at a national and E.U . level is evaluated, along with the degree of industry interest and involvement, and reasons are identified for successes or failures in the uptake of the results into management and policy. Finally, the question is posed whether the programme has been successful in improving the engagement of the fishing community in the science–management process and in fostering communication and greater trust between fishers, scientists and managers.

Species composition of skates (Rajidae) in commercial fisheries around the British Isles and their discarding patterns - J. F. Silva; J. R. Ellis; T. L. Catchpole (Journal of Fish Biology, 2012)
Recent regulations have required European nations to report commercial landings of Rajidae (skates) to species level since 2008. Morphological similarities between some species, variability in colouration and regional differences in common names may compromise the accuracy of some of these data. An increased proportion of rajid landings reported by the U.K. (England, Wales and Northern Ireland) are now reported to species level (42% in 2008, rising to 92% in 2010). Recent landings (2007–2010) of Rajidae by the U.K. indicated that the majority of reported landings were made by otter trawl (55·9%), tangle and gillnet (18·7%) and beam trawl (15·5%). Approximately 70% of recent landings originated from four ICES Divisions: the Irish Sea (VIIa), western English Channel (VIIe), Bristol Channel (VIIf) and southern North Sea (IVc). Recent species‐specific landings of Rajidae are appraised in terms of the species reported and the overall composition, and potential problems identified. Data from observer trips have been used to estimate the species composition of Rajidae taken in some of the main commercial fisheries operating around the British Isles, and these data are compared to landings. Although there was typically broad agreement between these data sets in terms of the main species landed, misidentification issues were apparent and Rajidae with highly patchy distributions may be under‐represented in observer data. Data from observer trips were also used to examine the discard and retention pattern. Most rajid species were first retained from total lengths, L T , of 27–34 cm, with 50% retention occurring at between 49 and 51 cm and near‐full retention at L T of 60–67 cm. Beam trawls captured a higher proportion of smaller individuals, whilst gillnets (>150 mm mesh size) caught proportionally more larger rajids.

Gear technology in Nephrops trawl fisheries - T. L. Catchpole; A. S. Revill (Reviews in Fish Biology and Fisheries, 2008)

Improved Recovery of Antibiotic-Stressed Microorganisms on Inclusion of Saponin in Aerobic Blood Culture Media - T. S. J. Elliott; C. M. Stevens; F. Macrae; I. T. Hart; D. E. Healing; M. Palmer; C. R. Catchpole (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Improved recovery of antibiotic-stressed microorganisms on inclusion of saponin in aerobic blood culture media - T. S. J. Elliott; C. M. Stevens; F. Macrae; I. T. Hart; D. E. Healing; M. Palmer; C. R. Catchpole (European Journal of Clinical Microbiology & Infectious Diseases, 1998)